A descriptive analysis of a novel intervention to help residents become evidence users. (October 2013) - Korownyk, Christina; Ross, Shelley; Ma, Victoria; Aaron, Sarah; Allan, G. Michael
<x xml:space="preserve">Abstract</x> Background and objectives: To evaluate the educational and clinical effectiveness of the 'Brief Evidence-Based Assessment of Research' (BEAR), a template to assist residents in searching, evaluating and integrating relevant medical literature into daily practice. Methods: We completed a descriptive analysis of BEARs submitted by first year residents between 2005 and 2007 at the University of Alberta Family Medicine Residency program. Results: 317 BEARs were analyzed. The most common type of question for which information was searched was therapy (59%). Residents searched Pubmed most often (38%) followed by Summary (i.e. Clinical Evidence) (22%) and Filtered sites (i.e. ACP Journal Club) (19%). Original research articles were the largest resource category used to answer questions (41%). Secondary peer-reviewed resources (filtered articles, summary sites, reviews/meta-analysis and guidelines) accounted for 48% of all resources used. 19% of residents reported a large change in practice with completion of the BEAR, 50% reported a small change, 12% stated they were reassured and 8% reported that the intervention was of no help to them. Conclusions: The BEAR facilitates the use of a variety of resources in answering clinical questions. 69% of users reported at least a small change in clinical practice, suggesting that the BEAR may be a useful tool in evidence-based resident education.